Dust‐free bleaching powder may not prevent symptoms in hairdressers with bleaching‐associated rhinitis. Issue 5 (30th September 2016) - Nielsen, Jörn; Nilsson, Patrik; Dahlman‐Höglund, Anna; Diab, Kerstin Kronholm; Albin, Maria; Kåredal, Monica; Jönsson, Bo; Wierzbicka, Aneta; Gudmundsson, Anders
Abstract : Objective: Hairdressers have an increased risk for airway symptoms especially when using hair‐bleaching powder containing persulfate. To minimize exposure, dust‐free bleaching powder(DFP) has been made available. We studied the effects of regular powder (RP) or DFP on the airway symptoms of hairdressers with hair‐bleaching associated rhinitis. Methods: Twelve hairdressers each performed three hair‐bleachings on a wig in an exposure chamber. Half of the subjects used RP and half used DFP. Exposure to persulfate and ammonia was measured. Before and after each bleaching, the participants stated their degree of airway symptoms on a visual analogue scale. Nasal lavage and blood were sampled before exposure, after the last bleaching, and in the morning after exposure to measure inflammatory markers. Results: Exposure to persulfate was higher when using RP compared to DFP, 22 (11‐55) vs. 12 (813) μg/m 3 ; median (min‐max). Exposure to ammonia did not differ between the groups. Both groups reported an increase in asthma‐like symptoms and this increase was significant. Neutrophils, lymphocytes, and monocytes increased after exposure in both groups; monocytes decreased the day after. In nasal lavage, IL‐8 was increased the morning after for both types of powder, and the increase was significant in the total group. IL‐6 increased immediately after exposure and the day after only in the group using RP. Conclusions: Although DFP powder emits lower levels of persulfate, effects are still elicited in symptomatic hairdressers.